Implementation model of data analytics as a tool for improving internal audit processes - Álvarez-Foronda, Rubén; De-Pablos-Heredero, Carmen; Rodríguez-Sánchez, José-Luis (Frontiers in Psychology, 2023)
The aim of this article is to understand the importance of internal audit departments today –as part of corporate governance and guardian of the organization’s culture and climate-, as well as the opportunities that new technologies offer to increase their effectiveness and efficiency. To this end, based on an exhaustive review of the literature, the concepts of internal audit and data analytics are related, and a framework is proposed for the implementation of a technology of these characteristics in an internal audit department.The results of the research show that those companies that invest resources in readapting their processes to technological change are likely to obtain better results than those organizations that keep their management procedures obsolete. Based on these results, it is concluded that there is a need to consider technological change in internal audit departments, specifically data analytics, as a means to increase the effectiveness and efficiency of audit processes.